Next steps for clinical translation of adenosine pathway inhibition in cancer immunotherapy - Riyue Bao; Aung Naing; Lawrence Fong; Jason J. Luke; Robert D. Leone; Ryan C. Augustin (Journal for ImmunoTherapy of Cancer)
Increasing evidence supports targeting the adenosine pathway in immuno-oncology with several clinical programs directed at adenosine A2 receptor (A2AR, A2BR), CD73 and CD39 in development. Through a cyclic-AMP-mediated intracellular cascade, adenosine shifts the cytokine and cellular profile of the tumor microenvironment away from cytotoxic T cell inflammation toward one of immune tolerance. A perpetuating cycle of tumor cell proliferation, tissue injury, dysregulated angiogenesis, and hypoxia promote adenosine accumulation via ATP catabolism. Adenosine receptor (eg, A2AR, A2BR) stimulation of both the innate and adaptive cellular precursors lead to immunosuppressive phenotypic differentiation. Preclinical work in various tumor models with adenosine receptor inhibition has demonstrated restoration of immune cell function and tumor regression. Given the broad activity but known limitations of anti-programmed cell death protein (PD1) therapy and other checkpoint inhibitors, ongoing studies have sought to augment the successful outcomes of anti-PD1 therapy with combinatorial approaches, particularly adenosine signaling blockade. Preliminary data have demonstrated an optimal safety profile and enhanced overall response rates in several early phase clinical trials with A2AR and more recently CD73 inhibitors. However, beneficial outcomes for both monotherapy and combinations have been mostly lower than expected based on preclinical studies, indicating a need for more nuanced patient selection or biomarker integration that might predict and optimize patient outcomes. In the context of known immuno-oncology biomarkers such as tumor mutational burden and interferon-associated gene expression, a comparison of adenosine-related gene signatures associated with clinical response indicates an underlying biology related to immunosuppression, angiogenesis, and T cell inflammation. Importantly, though, adenosine associated gene expression may point to a unique intratumoral phenotype independent from IFN-γ related pathways. Here, we discuss the cellular and molecular mechanisms of adenosine-mediated immunosuppression, preclinical investigation of adenosine signaling blockade, recent response data from clinical trials with A2AR, CD73, CD39 and PD1/L1 inhibitors, and ongoing development of predictive gene signatures to enhance combinatorial immune-based therapies.